Synthesis and properties of tetrathiafulvalenes bearing 6-aryl-1,4-dithiafulvenes - Yoshimura, Aya; Kimura, Hitoshi; Kagawa, Kohei; Yoshioka, Mayuka; Itou, Toshiki; Vasu, Dhananjayan; Shirahata, Takashi; Yorimitsu, Hideki; Misaki, Yohji (Beilstein Journal of Organic Chemistry, 2020)
Novel multistage redox tetrathiafulvalenes (TTFs) bearing 6-aryl-1,4-dithiafulvene moieties were synthesized by palladium-catalyzed direct C–H arylation. In the presence of a catalytic amount of Pd(OAc)2, P(t-Bu3)·HBF4, and an excess of Cs2CO3, the C–H arylation of TTF with several aryl bromides bearing 1,3-dithiol-2-ylidenes took place efficiently to produce the corresponding π-conjugated molecules. We also succeeded in the estimation of the oxidation potentials and number of electrons involved in each oxidation step of the obtained compounds by digital simulations.
Keywords: cross-conjugated systems; electrochemical properties; extended π-conjugation; digital simulation analysis; tetrathiafulvalene